On-line identification of P-glycoprotein substrates by monitoring of extracellular acidification and respiration rates in living cells - Seeland, Swen; Treiber, Alexander; Hafner, Mathias; Huwyler, Jörg (Biochimica et biophysica acta. Biomembranes, 2011)
The influence of P-glycoprotein (ABCB1) in drug resistance as well as drug absorption and disposition is an important factor to be considered during the development of new drugs. Thus, the early identification and exclusion of compounds showing a high affinity towards P-glycoprotein can help to select drug candidates. The aim of our study was to implement a label-free assay for the identification of P-glycoprotein substrates in living cells. For this approach, a multiparametric, chip-based sensor system was used to determine extracellular acidification, cell respiration and adhesion upon stimulation with P-glycoprotein substrates. Using L-MDR1 cells, a human P-glycoprotein overexpressing cell line, the influence of P-glycoprotein activity was determined for seven different compounds, demonstrating the applicability of the system for P-glycoprotein substrate identification. Effects were concentration dependent, as shown for the P-glycoprotein substrate verapamil, and were associated with cellular acidification and respiration. P-glycoprotein ATPase activation by verapamil could be described by a Michaelis-Menten type kinetic profile showing saturation at high substrate concentrations. The Michaelis-Menten constants KM were determined to be 0.92μM (calculated based on extracellular acidification) and 4.9μM (calculated based on cellular respiration). Control experiments using 100nM of the P-glycoprotein inhibitor elacridar indicated that the observed effects were related to P-glycoprotein ATPase activity. In contrast, wild-type LLC-PK1 cells not expressing P-glycoprotein were not responsive towards stimulation with different P-glycoprotein substrates. Summarizing these findings, the used microsensor system is a generic system suitable for the identification of P-glycoprotein substrates. In contrast to biochemical P-glycoprotein assays, activation of the drug efflux pump can be monitored on-line in living cells to identify P-glycoprotein substrates and to study the molecular mechanisms of adenosintriphosphate-dependent active transport.
Gesehen am 31.10.2022
Available online 22 March 2011